Prefrontal cortex afferents to the anterior temporal lobe in the Macaca fascicularis monkey. Issue 17 (7th July 2015) - Mohedano‐Moriano, Alicia; Muñoz‐López, Mónica; Sanz‐Arigita, Ernesto; Pró‐Sistiaga, Palma; Martínez‐Marcos, Alino; Legidos‐Garcia, María Ester; Insausti, Ana María; Cebada‐Sánchez, Sandra; Arroyo‐Jiménez, María Del Mar; Marcos, Pilar; Artacho‐Pérula, Emilio; Insausti, Ricardo
ABSTRACT The anatomical organization of the lateral prefrontal cortex (LPFC) afferents to the anterior part of the temporal lobe (ATL) remains to be clarified. The LPFC has two subdivisions, dorsal (dLPFC) and ventral (vLPFC), which have been linked to cognitive processes. The ATL includes several different cortical areas, namely, the temporal polar cortex and rostral parts of the perirhinal, inferotemporal, and anterior tip of the superior temporal gyrus cortices. Multiple sensory modalities converge in the ATL. All of them (except the rostral inferotemporal and superior temporal gyrus cortices) are components of the medial temporal lobe, which is critical for long‐term memory processing. We studied the LPFC connections with the ATL by placing retrograde tracer injections into the ATL: the temporal polar (n = 3), perirhinal (areas 35 and 36, n = 6), and inferotemporal cortices (area TE, n = 5), plus one additional deposit in the posterior parahippocampal cortex (area TF, n = 1). Anterograde tracer deposits into the dLPFC (A9 and A46, n = 2), the vLPFC (A46v, n = 2), and the orbitofrontal cortex (OF; n = 2) were placed for confirmation of those projections. The results showed that the vLPFC displays a moderate projection to rostral area TE and the dorsomedial portion of the temporal polar cortex; in contrast, the dLPFC connections with the ATL were weak. By comparison, the OFC and medial frontal cortices (MFC) showed dense connectivity with the ATL, namely, A13 with the temporopolar and perirhinal cortices. All areas of the MFC projected to the temporopolar cortex, albeit with a lower intensity. The functional significance of such paucity of LPFC afferents is unknown. J. Comp. Neurol. 523:2570–2598, 2015. © 2015 Wiley Periodicals, Inc.